Improving quality of care in inflammatory bowel disease: What changes can be made today?. (1st September 2014) - Panés, Julián; O'Connor, Marian; Peyrin-Biroulet, Laurent; Irving, Peter; Petersson, Joel; Colombel, Jean-Frédéric
Abstract: Background and aims: There are a number of gaps in our current quality of care for patients with inflammatory bowel diseases. This review proposes changes that could be made now to improve inflammatory bowel disease care. Methods: Evidence from the literature and clinical experience are presented that illustrate best practice for improving current quality of care of patients with inflammatory bowel diseases. Results: Best care for inflammatory bowel disease patients will involve services provided by a multidisciplinary team, ideally delivered at a centre of excellence and founded on current guidelines. Dedicated telephone support lines, virtual clinics and networking may also provide models through which to deliver high-quality, expert integrated patient care. Improved physician–patient collaboration may improve treatment adherence, producing tangible improvements in disease outcomes, and may also allow patients to better understand the benefits and risks of a disease management plan. Coaching programmes and tools that improve patient self-management and empowerment are likely to be supported by payers if these can be shown to reduce long-term disability. Conclusions: Halting disease progression before there is widespread bowel damage and disability are ideal goals of inflammatory bowel disease management. Improving patient–physician communication and supporting patients in their understanding of the evidence base are vital for ensuring patient commitment and involvement in the long-term management of their condition. Furthermore, there is a need to create more centres of excellence and to develop inflammatory bowel disease networks to ensure a consistent level of care across different settings.